ANALISIS TREN DAN ARAH DIGITALISASI KEARSIPAN DI INDONESIA MENUJU TATA KELOLA ARSIP MODERN TERINTEGRASI - Merry Susana (Publikasi Inspirasi Indonesia, 2025)
The advancement of information technology has driven significant changes in archival management, shifting from manual systems to integrated digitalization. This study aims to analyze the trends in archival digitalization in Indonesia and identify strategic directions toward modern, integrated archival governance across institutions. A qualitative descriptive approach was employed, with data collected through literature review, policy document analysis, and expert interviews. The findings reveal that archival digitalization in Indonesia is progressively developing, as evidenced by the adoption of various archival information systems such as SIKD and e-Arsip in both governmental and private institutions. However, implementation still faces challenges, particularly in human resource capacity, technological infrastructure, metadata standardization, and system interoperability. Strategic directions identified include strengthening regulations, accelerating system integration based on government service architecture, enhancing human resource capacity, and developing a national platform supporting the One Data Indonesia policy. These findings are expected to serve as a reference for policymakers and archival practitioners in accelerating the transformation toward effective, efficient, and sustainable archival governance.